IMPROVING STUDENTS' UNDERSTANDING OF CONCEPTS THROUGH THE IDEA LEARNING MODEL - Hadi, Sunandar Azma’ul; Asyari, Dian Noer (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to increase students' understanding of concepts regarding the transport of substances in cells through the IDEA learning model. The research subjects chosen in this study were 23 students of the Class A Physics Study Program, Semester 1, Mataram State Islamic University (UIN), using the One-Group Pretest-Posttest Design. The data analysis technique in this research uses quantitative description. The results of this research show that the IDEA learning model is effectively used to increase students' understanding of concepts. This is proven by all students who took the test using the concept understanding test instrument getting classical completion results with a completion percentage of 82.6%. 4 students did not complete due to the learning productivity factors of the students concerned, such as learning independence and a weak understanding of basic concepts. The results of this research prove that the IDEA learning model is effectively used to increase students' understanding of concepts regarding the transport of substances in cells. It is hoped that the results of this research can then be implemented by lecturers to help students improve their understanding of concepts in biology material.